Should Government Facilitate Voluntary Pension Plans? - Norma L. Nielson (The School of Public Policy Publications, 2010)
Several proposals have surfaced recently that government develop and offer some sort of voluntary pension plan (VPP). This paper examines areas of public policy on pensions where changes should take place with or without the development of a VPP, including those that promote greater harmonization, portability, and labour mobility. Similarly, the challenges of inertia and annuitization are areas in which a VPP is only one of several available policy devices. In the final analysis, two key arguments provide the only compelling reasons to support the establishment of large, economically efficient funds: that their assets could be managed professionally and efficiently and that they could reduce the distraction from employers’ primary goals. Neither of these arguments, however, offers convincing evidence that VPPs should be developed by government rather than by the private sector. Ultimately, the marketplace will determine whether the additional option of a VPP is needed and whether it is offered on terms that make it more attractive than the other available alternatives.